Noise-Referred Energy-Proportional Routing with Packet Length Adaptation for clustered sensor networks. (16th July 2008) - Chen, Chao-Lieh; Lee, Jeng-Wei; Su, Wei-Tsung; Horng, Mong-Fong; , Yau-Hwang Kuo
The optimal Packet Length Adaptation (PLA) for throughput and energy utilisation in wireless networks with and without re-transmission is respectively derived and developed. A noise referred distance model of wireless channels is developed for accurate estimation of the dissipated proportion in the residual energy. To balance the load, the Energy-Proportional Routing (EPR) determines whether a cluster head or a node should either undertake forwarding tasks or transmit data to intermediate hops. The cooperation of PLA with the EPR algorithm effectively extends lifetime while throughput and energy utilisation are maximised even the distribution of channel noise is so unpredictable.